Peeling the Layers Away: The Genomic Characterization of Bacillus pumilus 64-1, an Isolate With Antimicrobial Activity From the Marine Sponge Plakina cyanorosea (Porifera, Homoscleromorpha) - Freitas-Silva, Jéssyca; de Oliveira, Bruno Francesco Rodrigues; Vigoder, Felipe de Mello; Muricy, Guilherme; Dobson, Alan D. W.; Laport, Marinella Silva (Frontiers in Microbiology, 2021)
Bacillus pumilus 64-1, a bacterial strain isolated from the marine sponge Plakina cyanorosea, exhibits antimicrobial activity against both pathogenic and drug-resistant Gram-positive and Gram-negative bacteria. This study aimed to conduct an in-depth genomic analysis of this bioactive sponge-derived strain. The nearly complete genome of strain 64-1 consists of 3.6 Mbp (41.5% GC), which includes 3,705 coding sequences (CDS). An open pangenome was observed when limiting to the type strains of the B. pumilus group and aquatic-derived B. pumilus representatives. The genome appears to encode for at least 12 potential biosynthetic gene clusters (BGCs), including both type I and type III polyketide synthases (PKS), non-ribosomal peptide synthetases (NRPS), and one NRPS-T1PKS hybrid, among others. In particular, bacilysin and other bacteriocin-coding genes were found and may be encharged of the detected antimicrobial action. Strain 64-1 also appears to possess a broad repertoire of genes encoding for plant cell wall-degrading carbohydrate-active enzymes (CAZymes). It was also found a myriad of genes which may be involved in various process required by the strain in its marine habitat, such as those encoding for osmoprotectory transport systems and the biosynthesis of compatible solutes. Several heavy metal tolerance genes are also present, together with various mobile elements including a region encoding for a type III-B Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) region, four prophage segments and transposase elements. This is the first report on the genomic characterization of a cultivable bacterial member of the Plakina cyanorosea holobiont.